2020
DOI: 10.3390/molecules25030674
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Study of Anti-Ferroptosis and Antioxidant Mechanisms of Butein and (S)-Butin

Abstract: To elucidate the mechanism of anti-ferroptosis and examine structural optimization in natural phenolics, cellular and chemical assays were performed with 2′-hydroxy chalcone butein and dihydroflavone (S)-butin. C11-BODIPY staining and flow cytometric assays suggest that butein more effectively inhibits ferroptosis in erastin-treated bone marrow-derived mesenchymal stem cells than (S)-butin. Butein also exhibited higher antioxidant percentages than (S)-butin in five antioxidant assays: linoleic acid emulsion as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 101 publications
0
21
0
Order By: Relevance
“…Curcumin is considered suitable for the prevention and reduction of the risk of DM complications, due to its anti-inflammatory and antioxidant activity [80]. Butein, an antioxidant polyphenol, inhibits the formation of NO in vitro, protects pancreatic β-cells under conditions of excessive inflammation, and can be used to prevent the progression of DM1 [65]. Resveratrol modulates the expression of genes associated with the DM2 development by inducing the expression of several β-cell genes and insulin expression in pancreatic α-cells [50].…”
Section: Deactivation Of the Insulin Signaling Pathwaymentioning
confidence: 99%
“…Curcumin is considered suitable for the prevention and reduction of the risk of DM complications, due to its anti-inflammatory and antioxidant activity [80]. Butein, an antioxidant polyphenol, inhibits the formation of NO in vitro, protects pancreatic β-cells under conditions of excessive inflammation, and can be used to prevent the progression of DM1 [65]. Resveratrol modulates the expression of genes associated with the DM2 development by inducing the expression of several β-cell genes and insulin expression in pancreatic α-cells [50].…”
Section: Deactivation Of the Insulin Signaling Pathwaymentioning
confidence: 99%
“…These data suggested that ( i ) chebulagic acid and chebulinic acid are very strong antioxidants, and ( ii ) the relative antioxidant levels of chebulagic acid and chebulinic acid correlate with their ferroptosis inhibition levels ( Figure 2 and Figure 3 ). Therefore, on the basis of the above results and previous studies [ 22 , 23 , 24 , 25 , 44 , 45 ], the ferroptosis inhibition of both tannins was presumed to be via an antioxidant mechanism, attributed to the presence of multiple phenolic –OH groups [ 21 , 46 , 47 ]. It is worth mentioning that, the so-called “antioxidant mechanism” also includes SET-PT (single electron transfer–proton transfer) and SPLET (sequential proton loss electron transfer), apart from the above hydrogen atom transfer [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 60%
“…Therefore, there is an urgent need to screen for safe and effective ferroptosis inhibitors from natural products. Previous studies have stated that flavonoid and monostilbenes could act as natural ferroptosis inhibitors [ 22 , 23 , 24 , 25 ], whereby the ferroptosis-inhibitory effect may arise from the presence of the phenolic –OH group.…”
Section: Introductionmentioning
confidence: 99%
“…Fer‐1 was not evaluated for its insolubility (Table 1). However, in the FRAP and ABTS .+ ‐trapping assays, Fer‐1 increases in a dose‐dependent manner, suggesting the ET potential of Fer‐1, [44–47] which confirms the recycling of the catalyst (Figure 6). Similar effectiveness is observed for the two gallotannins.…”
Section: Resultsmentioning
confidence: 71%